Mistake, Ignorance, Expectation of Benefit, and the Modern Law of Confessions - George E. Dix (Washington University Law Quarterly, 1975)
This Article is an examination of the legal significance of several possible characteristics of a confessing defendant’s state of mind: his ignorance or mistake concerning the facts or the law relating thereto (whether influenced by affirmative and intentional deception by law enforcement authorities, by good faith promises and representations of such persons, or by other factors) and reliance upon expectations that he will in some way benefit from the confession. The thesis presented here is that the lack of clarity in regard to these issues results from the selection of legal vehicles manifestly inappropriate for dealing with the underlying problems and that such selection has been due largely to an unwillingness to deal specifically with the issues.
Keywords: Admissibility of evidence; Confessions; Mistake